The Analysis of Sufism morals Morals Course Effect on the Attitude of the Students in the Islamic English Education Study Program - Qomariah, Zaitun; Firdaus, Rizki Alfajri (YPI Ulul Albab, 2024)
This study aims to analyze the influence of Sufism morals (Akhlak Tasawuf) courses on the attitudes of students in the Islamic English Education Study Program. This research method uses a qualitative approach with data analysis from library sources. The results of the study show that Sufism morals attitude courses have a positive impact on student attitudes, with an increase in spiritual awareness and sensitivity to attitude values. The implications of this finding highlight the importance of integrating Sufism morals and moral education into the curriculum to strengthen the character and morality of students. Overall, this study provides a deep understanding of the role of Sufism morals attitude courses in shaping students' attitudes and values ​​in the context of Islamic English education.